Messenger RNA‐based vaccines: progress, challenges, applications. (25th July 2013) - Kramps, Thomas; Probst, Jochen
<x xml:space="preserve">Abstract</x> Twenty years after the demonstration that messenger RNA (mRNA) was expressed and immunogenic upon direct injection in mice, the first successful proof‐of‐concept of specific protection against viral infection in small and large animals was reported. These data indicate wider applicability to infectious disease and should encourage continued translation of mRNA‐based prophylactic vaccines into human clinical trials. At the conceptual level, mRNA‐based vaccines—more than other genetic vectors—combine the simplicity, safety, and focused immunogenicity of subunit vaccines with favorable immunological properties of live viral vaccines: (1) mRNA vaccines are molecularly defined and carry no excess information. In the environment and upon physical contact, RNA is rapidly degraded by ubiquitous RNases and cannot persist. These characteristics also guarantee tight control over their immunogenic profile (including avoidance of vector‐specific immune responses that could interfere with repeated administration), pharmacokinetics, and dosing. (2) mRNA vaccines are synthetically produced by an enzymatic process, just requiring information about the nucleic acid sequence of the desired antigen. This greatly reduces general complications associated with biological vaccine production, such as handling of infectious agents, genetic variability, environmental risks, or restrictions to vaccine distribution. (3) RNA can be tailored to provide potent adjuvant stimuli to the innate immune system by direct activation of RNA‐specific receptors; this may reduce the need for additional adjuvants. The formation of native antigen in situ affords great versatility, including intracellular localization, membrane association, posttranslational modification, supra‐molecular assembly, or targeted structural optimization of delivered antigen. Messenger RNA vaccines induce balanced immune responses including B cells, helper T cells, and cytotoxic T lymphocytes, rendering them an extremely adaptable platform. This article surveys the design, mode of action, and capabilities of state‐of‐the‐art mRNA vaccines, focusing on the paradigm of influenza prophylaxis. WIREs RNA 2013, 4:737–749. doi: 10.1002/wrna.1189 For further resources related to this article, please visit the WIREs website. Conflict of interest: The authors have declared no conflicts of interest for this article.